An exploration of individual, job, and organizational characteristics associated with district research leaders’ knowledge brokering work - Shewchuk, Samantha Jo; Farley-Ripple, Elizabeth (Education Policy Analysis Archives, 2022)
The role of district research leaders (DRLs) in central offices has emerged as a strategy for improving the creation, flow, and use of research knowledge in decision-making. However, there is limited information about the responsibilities, opportunities, and challenges inherent in these roles. This exploratory qualitative study features document analysis to examine the individual backgrounds, job demands, and organizational contexts of DRLs. The result of this study suggest that multiple pathways to the DRL role exist, but few include formal training in knowledge brokering. Further findings suggest that DRL jobs are complex and entail diverse tasks, but share a focus on research leadership and coordination, identifying and obtaining relevant research information, and facilitating evidence-informed change. Moreover, organizational contexts varied in supportiveness for knowledge brokering work. Overall, there was limited evidence of alignment across individual, job, and organizational characteristics, signaling an opportunity to better define and support those in DRL roles.